2013
DOI: 10.1002/cjce.21831
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced extraction of 2,3‐butanediol by medley solvent of salt and n‐butanol from aqueous solution

Abstract: Enhanced extraction of 2,3-butanediol by adding salt into solvent n-butanol has been studied in this paper. Ternary phase diagrams for 2,3-butanediol + water + salt have been determined. The influences of phase ratio, type of salts and salt content on distribution coefficient and selectivity have also been investigated systematically. With phase ratio of 0.75 (w/w) and salt content of K 2 HPO 4 of 25% (w/w), the distribution coefficient, separation factors and recovery yield in a single extraction process by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This study reported K d around 8 for 2,3‐butanediol using ethanol as solvent. Another study reported K d and α value of 5.2 and 34, respectively, with 80% extraction yield using 1‐butanol as solvent and potassium phosphate as salt . To achieve this high recovery yield larger amounts (>25%) of salts were used, making the process uneconomical and less attractive from an industrial‐scale perspective .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study reported K d around 8 for 2,3‐butanediol using ethanol as solvent. Another study reported K d and α value of 5.2 and 34, respectively, with 80% extraction yield using 1‐butanol as solvent and potassium phosphate as salt . To achieve this high recovery yield larger amounts (>25%) of salts were used, making the process uneconomical and less attractive from an industrial‐scale perspective .…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported K d and α value of 5.2 and 34, respectively, with 80% extraction yield using 1‐butanol as solvent and potassium phosphate as salt . To achieve this high recovery yield larger amounts (>25%) of salts were used, making the process uneconomical and less attractive from an industrial‐scale perspective . Aqueous two phase extraction studies on 2,3‐butanediol extraction reported K d 9.9 and 7.1 for 2,3‐butanediol using isopropanol/ammonium sulfate and ethanol/ammonium sulfate systems .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these papers, ethanol and isopropanol as water-miscible alcohols, and dipotassium hydrogen phosphate and ammonium sulfate as inorganic salts were used. Wu et al [21] employed the dipotassium hydrogen phosphate/1-butanol system for the extraction of 2,3-BD, although 1-butanol is not fully water-miscible.…”
Section: Introductionmentioning
confidence: 99%